2017
DOI: 10.3892/mmr.2017.6181
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for the establishment of a model of Graves' disease in BALB/c mice

Abstract: The present study aimed to develop a stable Graves' disease (GD) model in BALB/c mice by immunization and electroporation (EP). A total of 90 mice were divided into experimental (n=50), control (n=20) and blank (n=20) groups. The recombinant plasmid pcDNA3.1/thyroid-stimulating hormone (TSH) receptor 268 was constructed and injected into the bilateral gastrocnemius of experimental group mice at weeks 1, 4, 7 and 10. Equal volumes of saline were injected into the control and blank groups at the same time. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The incidence of the disease is an important sign to evaluate the successful of a model that thyroid alterations and hyperthyroidism were the key factors in the GD model [15]. In 2002, the incidence of GD in BALB/c mice was about 50-60% [8]. Some researchers improved the incidence of GD by combining Ad-TSHR289 immunization with other methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of the disease is an important sign to evaluate the successful of a model that thyroid alterations and hyperthyroidism were the key factors in the GD model [15]. In 2002, the incidence of GD in BALB/c mice was about 50-60% [8]. Some researchers improved the incidence of GD by combining Ad-TSHR289 immunization with other methods.…”
Section: Discussionmentioning
confidence: 99%
“…DCs infected with AdTSHR289 immunized in BALB/c mice with a disease induction rate of about 70% [16]. The method of TSHR genetic immunization and vivo electroporation was also widely used [7,8,17]. A study recently reported that over 80% of immunization mice have developed to GD and the incidence of goiter was more than 90% with immunization and electroporation [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All 70 female BALB/c mice were injected with pcDNA 3.1/TSHR 289 into the bilateral gastrocnemius and electroporated (EP) every 3 weeks 4 times. The protocol for establishing the GD mouse model was described in our previous article [13]. This work was approved by the Ethics Committee of Tianjin Medical University General Hospital (NO.…”
Section: Establishment Of the Gd Mouse Modelmentioning
confidence: 99%